Benzo-Fused 7-Oxabicyclo[2.2.1]heptane-2,3-diol Derivatives as Universal Linkers for Solid-Phase Oligonucleotide Synthesis - Fuchi, Yasufumi; Yamamoto, Kazuki; Ito, Yuta; Hari, Yoshiyuki (Synthesis, 2023)
In solid-phase oligonucleotide (ON) synthesis, especially for 3′-modified ONs, a universal linker attached to a solid support is widely used. In this study, benzo-fused 7-oxabicyclo[2.2.1]heptane-2,3-diol derivatives are designed, synthesized, and evaluated as universal linkers. The designed linkers show reactivity comparable to that of a conventional universal linker for releasing the desired ONs. Additionally, these materials exhibit a more robust structure under basic conditions, as generally used in ON synthesis, and hydrophobic properties relative to the conventional universal linker. Notably, when diphenyl-substituted (terphenyl) and phenanthrene-type (PT) linkers are used, cyclic phosphodiesters derived from linker units as byproducts, which are produced by release of ONs from the linker units, are detected in the HPLC chromatograms. The PT linker is applicable to various ON syntheses using controlled pore glass (CPG) and polystyrene (PS) resins. These results demonstrate that the PT linker can serve as an alternative to conventional universal linkers.
Keywords: solid-phase synthesis; universal linker; oligonucleotides; benzo-fused 7-oxabicyclo[2.2.1]heptane-2,3-diol; phenanthrene